Perceived health and interaction with healthcare workers of a hard-to-reach group in a Roman suburb. (20th October 2021) - Caminada, S; Turatto, F; Jaljaa, A; Mazzalai, E; Giannini, D; Iorio, S; Errigo, M; Paglione, L; Marceca, M; Brandimarte, A
Abstract: : Previous studies have showed that people living in Bastogi - a segregated and deprived peripheral area of Rome- have difficulties in accessing and relating to health services. Our aim was to analyze the health perception, health-related behaviors, and the interaction between healthcare professionals and the census population living in Bastogi, compared to the population living in the area of the same local health unit, ASL Roma 1 (hereafter ASL). The PASSI survey (from the Italian Surveillance System) was administered by phone and through door-to-door interviews to a sample of 210 residents of Bastogi. Data were analyzed and compared to the ones of the ASL collected in 2017-2018. Descriptive and univariate analysis were performed with STATA 13. P-values ≤ 0.05 were considered statistically significant. The socio-economic indicators, acknowledged determinants of health inequalities, showed a worse condition for the inhabitants of Bastogi. There was a significantly higher proportion of foreign and unemployed residents in Bastogi, with a lower educational level compared to the ASL. 58.1 % of the Bastogi group claimed their health to be good/very good (ASL: 71.6%; p = 0.000). 56.2% of the respondents from Bastogi were current smokers (ASL: 25.8%; p = 0.000). Risk factors for and prevalence of chronic diseases were significantly higher in Bastogi. The proportion of respondents who stated they had not had any recent contact with health professionals was significantly higher, and mammogram screening uptake was lower (75.3%; ASL: 90.4%; p = 0.001). Despite their lower help-seeking behavior, our study pointed out that the respondents from Bastogi who had had a contact with a health professional reported a higher perceived interest about their health than in the ASL. Further studies are needed to investigate whether this attention is attributable to the higher prevalence of chronic diseases or to the health professional's awareness of vulnerability of a hard-to-reach group. Key messages: The population from Bastogi is marginalized and hard-to-reach: we found a worse overall self- reported health condition, a worse help-seeking behavior and a lack of reliance on health professionals. The PASSI survey administration has led to a greater involvement of the competent health institution, which resulted in the introduction of a community nurse and a Single Access Point.